2021
DOI: 10.1002/qua.26833
|View full text |Cite
|
Sign up to set email alerts
|

Dipole transition‐matrix elements and oscillator strengths for the C4+doubly excited states with Coulomb and screened Coulomb (Debye–Hückel) potentials

Abstract: The dipole transition-matrix elements (DTMEs) and oscillator strengths (OSs) for the doubly excited states (DESs) in heliumlike carbon are investigated using the correlated exponential wavefunctions (CEW). The interactions between the charged particles are taken care of by using both Coulomb and screened Coulomb (Debye-Hückel) poten-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In recent years, with the gradual development of plasma technology, the study on the structural properties of atomic and molecular systems under the influence of external environments is one of the hot research areas [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Several studies on the atomic systems under Debye screening and modified Debye screening are reported [15][16][17][18][19][20][21][22]. The modified Debye-Hückel potentials (MDHP) or particularly the exponential-cosine-screened Coulomb potential (ECSCP) are used to model the Quantum plasmas which are widely found in laser plasmas [23,24] and nanoscale objects [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the gradual development of plasma technology, the study on the structural properties of atomic and molecular systems under the influence of external environments is one of the hot research areas [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Several studies on the atomic systems under Debye screening and modified Debye screening are reported [15][16][17][18][19][20][21][22]. The modified Debye-Hückel potentials (MDHP) or particularly the exponential-cosine-screened Coulomb potential (ECSCP) are used to model the Quantum plasmas which are widely found in laser plasmas [23,24] and nanoscale objects [25].…”
Section: Introductionmentioning
confidence: 99%
“…Muonic molecular ions, as a branch of exotic atoms, have a wide range of applications in nuclear physics, condensed matter physics, and atomic-molecular physics. With the recent development of muon catalytic fusion [32,33], Muon Spin Rotation technology [34], muon spectroscopy experiments [35], and advancement in atomic and molecular systems under screening environments ( [1,30,[36][37][38], references therein), it is of great interest to investigate the bound states, and resonance states of exotic muonic-molecular systems under the influence of ECSCP, which can provide benchmark data for future studies on this topic. Furthermore, it is also relevant to search Borromean state, a bound state of three quantum particles that falls apart if one particle is taken away, for the P-state of the exotic molecular ions interacting with MDHP or ECSCP.…”
Section: Introductionmentioning
confidence: 99%